Design and Development of Customer Relationship Management in a Construction Company - Ni Kadek Puja Ari Pertiwi; Ni Putu Sutramiani; K Suar Wibawa (P3M Politeknik Negeri Bengkalis, 2025)
CV. Puspa Karya is a construction company that faces challenges in customer management and marketing activities. This study aims to design and implement a Customer Relationship Management (CRM) system using the Flectra framework to support marketing, sales, and customer‐service processes more effectively, with the specific objectives of improving both operational efficiency and customer satisfaction. The research employs the Accelerated SAP (ASAP) methodology, chosen for its systematic, result‐oriented approach that is well suited to projects requiring structured planning and rapid execution. ASAP was applied in five tailored phases: Project Preparation, Business Blueprint, Realisation, Final Preparation, and Go-Live & Support. The developed system was validated through User Acceptance Testing (UAT), achieving a final score of 167. User satisfaction was further assessed via the Post-Study System Usability Questionnaire (PSSUQ), yielding an overall mean score of 1.60 on a 1–7 scale (where lower scores indicate higher satisfaction): System Usefulness 1.55, Information Quality 1.66, and Interface Quality 1.61. These results exceed typical industry benchmarks for comparable systems. The implications include qualitative enhancements in customer‐service quality and quantitative gains in process speed and prospect‐tracking accuracy, leading to heightened operational professionalism, increased client trust, and stronger potential for customer loyalty.